IMPROVING READING ABILITY AND MOTIVATION WITH A SMART APP CREATOR - Wiharmansi Wiharmansi; Artanti Puspita Sari; Hanny Yukamana (Universitas Muhammadiyah Makassar, 2023)
The goal of this study was to discover and analyze the process of using smart app creator to improve the reading ability of eleventh grade engineering students at SMK Negeri 3 OKU Selatan. This study employed the classroom action research method, in which the researcher collaborates with another English teacher. This study was carried out in three cycles in accordance with the Kemmis and Taggart action research methodology. The study's findings revealed that students' reading abilities and motivation had improved. The minimal completion score for the English lesson was 70. Identifying 15 students, or 50% of the class, who meet the minimum completion criteria in cycle 1. Twenty students, or 66% of the class, passed the cycle 2 finding test's minimum completeness requirements, and 26 students, or 86% of the class, passed the cycle 3 finding test's minimum completeness criteria. Students' reading abilities improved from cycle 1 to cycle 2. Reading skills improved by 16% between cycles 1 and 2, and 20% between cycles 2 and 3. Students' participation in the teaching-learning process increased, indicating an increase in students' motivation.